The effectiveness of writing emotional disclosure on the reduction of depression, anxiety, and stress among veterans with post-traumatic stress disorder - F Monazamitabar; M Ahmadi Tahoor Soltani; R Bagherian Sararoodi; M Behboodi (فصلنامه ابن سینا, 2015)
Background: Emotional disclosure enhances mental health, improve the immune system, and reduce physical problems. The aim of present study was to investigate the effectiveness of emotional disclosure on the reduction of depression, anxiety and stress symptoms among veterans with post-traumatic stress disorder (PTSD).